2015
DOI: 10.1590/s0102-6720201500s100005
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein in Diabetic Patients Before Gastric Bypass as a Possible Marker for Postoperative Complication

Abstract: Background: Obesity and type 2 diabetes mellitus are associated to inflammatory state, which can be set off by the adipose tissue, once it is a metabolically active organ that can cause a chronic mild inflammatory state. Aim: To evaluate the correlation between preoperative C-reactive protein and postoperative complications risk in obese patients (grades II and III) after Roux-en-Y gastric bypass, with and without type 2 diabetes mellitus. Methods : Between 2008 and 2013 were analysed 209 patients (107 with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Sigalet et al (36) also revealed that pediatric patients with active Crohn's disease presented significantly lower postprandial GLP-2 levels than healthy controls. Although the inflammation is supposed to be much more intense in inflammatory bowel diseases, obesity and T2D are also associated with a low-grade chronic inflammatory state (37)(38)(39)(40) . In fact, the discrepancy in CRP levels among the groups along with the differences in the GLP-2 levels observed in the present study tend to signal that this inflammatory state may also play a significant role in this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Sigalet et al (36) also revealed that pediatric patients with active Crohn's disease presented significantly lower postprandial GLP-2 levels than healthy controls. Although the inflammation is supposed to be much more intense in inflammatory bowel diseases, obesity and T2D are also associated with a low-grade chronic inflammatory state (37)(38)(39)(40) . In fact, the discrepancy in CRP levels among the groups along with the differences in the GLP-2 levels observed in the present study tend to signal that this inflammatory state may also play a significant role in this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Such increase can be explained, since the rapid weight loss that occurs in the first 30 days promotes necroinflammatory activity in the liver, consequently increasing the CRP values 32 . Lins et al 18 associated high preoperative CRP levels with complications after BGYR.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a chronic disease characterized by excess body fat, which causes injury to the individual 1 . It has grown all over the world, both in developed and underdeveloped countries, with high costs in the treatment of its complications 18 , 27 , 30 . The World Health Organization estimates that each year 2.8 million people die as a result of being overweight or obese 32 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations